OR38. Hematological Parameter of Contrast Induced Acute Kidney Injury in ST Elevation Myocardial Infarction Patient Underwent Percutaneous Coronary Intervention. (23rd November 2021) - Widyastuti, W; Hanika, R; Syukri, M; Syafri, M
Abstract: Aim: To determine the relationship of Neutrophil/Lymphocyte Ratio (NLR), Platelet/Lymphocyte Ratio (PLR) as simple inflammatory parameter to incident of Contrast Induce - Acute Kidney Injury (CI-AKI) in ST Elevation Myocardial Infarction (STEMI) patient underwent Percutaneous Coronary Intervention (PCI). Method and Result: We collected laboratory and angiographic data of 113 consecutive STEMI patient that treated with PCI in M. Djamil Hospital Padang since April 2020 – April 2021. CI-AKI define as increasing creatinine serum 25% or 0, 5 gr/dl over 48 hours after contrast administration. Patient with end stage renal failure were exclude. In this study we found 17.6 % patient developed CI-AKI after PCI. These patients have older age (mean 61 ± 8.7 years) with hypertension as majority of risk factor (65%). PLR and NLR were higher in CI-AKI group (220.11 ± 144.57; 7.49 ± 5.36) with significant differences in PLR (p < 0.08). Hemoglobin was lower in CI-AKI group (mean 12.56 ± 1.50) and amount of contrast used during PCI were more in CI-AKI group (mean 135.75 ± 27.63) but there was no significant differences. Conclusion: STEMI patient who underwent PCI with higher baseline PLR and NLR value have higher incident of CI-AKI. PLR have the most significant correlation to incident of CI -AKI in this population.